ANALISIS MANAJEMEN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PERUSAHAAN PAVING SURABAYA 2 DI PAMEKASAN - Ria Rachmawati (Assyarikah: Journal of Islamic Economic Business, 2022)
Inventory management is a very important managerial function in the company's operations. Without inventory, business actors are faced with the risk that a company cannot meet the needs and desires of its customers, but if the company invests too much funds in inventory, it will cause excessive storage costs. This study aims to determine the amount of raw material inventory that is economical, to know the amount of raw material inventory to be provided, and to find out when to reorder raw materials at Surabaya paving company 2. This type of research is a descriptive quantitative research using the EOQ (Economic Order) method. ). Quantity). The data collection technique used is documentation. The results showed that the EOQ (Economic Order Quantity) method was more economical than company policy. If the company uses the EOQ method, the economical supply of sand in 2022 is 152 m^3, the frequency of purchases is 5 times, with a total inventory cost of IDR 17,329,287, the most economical supply of cement in 2022 is 2,726 sacks, the frequency of purchases is 2 times, with a total inventory cost of IDR 6,936,696, and the economical mil inventory in 2022 is 316 sacks, the frequency of purchases is 2 times, with a total inventory cost of IDR 7,955,087. The amount of sand safety stock that must be provided is 21 m^3, cement is 134 sacks, and mil is 33 sacks. The right time to restock is when the raw materials are 33 m^3 of sand, 190 sacks of cement, and 41 sacks of mil.Â